Effectiveness of Single Garlic Extract on Fatty Liver and Liver Enzymes in Rattus Norvegicus Wistar - Syahputra, Fahmi; Suandy, Suandy; Chiuman, Linda (Jurnal Ners, 2025)
This study investigated the hepatoprotective efficacy of ethanol-extracted single garlic (EEBPT) on fatty liver and hepatic enzymes in rats. A true experimental design with pretest-posttest control group approach was employed. Twenty-four male Wistar rats (Rattus norvegicus) were randomly allocated into four groups: negative control (distilled water), positive control (simvastatin 2.1 mg/kg body weight), low-dose EEBPT (200 mg/kg body weight), and high-dose EEBPT (400 mg/kg body weight). All animals received high-fat diet supplementation for four weeks. Serum aspartate aminotransferase (SGOT/AST) and alanine aminotransferase (SGPT/ALT) were measured on days 0, 14, 21, and 28. Hepatic histopathology was assessed using hematoxylin and eosin staining. One-way ANOVA with Tukey post-hoc test and Kruskal-Wallis test were applied for statistical analysis (p<0.05). Results demonstrated that high-dose EEBPT significantly reduced SGOT and SGPT levels equivalent to simvastatin treatment and ameliorated hepatic steatosis, hepatocyte ballooning, and inflammatory infiltration. Ethanol-extracted single garlic at 400 mg/kg body weight exhibited hepatoprotective effects comparable to conventional statin therapy through antioxidative and anti-inflammatory mechanisms. Garlic extract represents a promising natural hepatoprotective agent for NAFLD management